Current principles and practices of telemedicine and e-health - Latifi, Rifat (Studies in health technology and informatics ;, 2008)
This book represents the most current development on the expanding and changing field of telemedicine and e-health, especially in the developing countries. Many things have changed since the publication of the first book in 2004 (""Establishing Telemedicine in Developing Countries: From Inception to Implementation""). Telemedicine has become more popular, and still continues to grow. While there are many good books and materials on telemedicine, this publication can be seen as a work of reference for all of those who want to practice telemedicine and e-health, particularly in developing countr.